Detection of Simonsiella spp. in the Vagina of Lions and Leopard in Oestrus. (1st September 2018) - Callealta, Isabel; Ganswindt, Andre; Goncalves, Sara; Mathew, Abraham; Lueders, Imke
Contents: Reports of the vaginal flora of wild cats such as lions or leopards are scarce. The micro‐organisms most commonly found in the vagina of clinically healthy cats are aerobic bacteria such as coagulase‐negative Staphylococcus, Streptococcus canis, and Escherichia coli . Simonsiella spp are large Gram‐negative bacteria belonging to the Neisseriaceae family, typically found in the oral cavity and upper respiratory tract of many species. To date, there are no reports of the detection of Simonsiella spp in the vaginal flora of any felid. For a period of six months, daily behaviour monitoring was performed on six captive lionesses at a South African conservation centre, in parallel with the collection of vaginal swabs and interpretation of the resultant vaginal cytologies every other day. Oestrus was identified by typical female reproductive behaviours, as well as by enlarged and separated vulvar lips, and a predominant proportion of superficial cornified cells, clearing of the background, and high bacterial presence in the vaginal smear. Simonsiella spp were identified by their characteristic morphology in 58% (60 of 103) of the vaginal samples collected during oestrus. They were also found in oral swabs of three out of three lions tested. Additionally, Simonsiella spp were opportunistically found in a vaginal smear from a zoo housed female Sri Lankan leopard in oestrus, during a routine reproduction assessment. The finding of Simonsiella spp may be more common than previously suspected, transitory, and without detectable clinical relevance. A connection between occurrence of these bacteria and oestrus was apparent.